Mechanistic investigation of formation of highly-dispersed silver nanoparticles using sea buckthorn extract. (19th February 2023) - Kaur, Hardeep; Anand, Vivek; Sharma, Ajay; Verma, Meenakshi; Sareen, Shweta; Mehta, Surinder Kumar; Mutreja, Vishal
Abstract: Nowadays, the greener pathways for the synthesis of nanostructures are being explored. The extracts of different parts of plants viz leaves, stems, and roots have been investigated. However, these extracts have been prepared by simply boiling or microwaving, or sonicating the parts of plants with water. Therefore, to have deeper insight and to investigate the full potential of plant extracts, serial extraction of leaves of sea buckthorn ( Hippophae rhamnoides L. ) which is a medicinally important plant was attempted using the soxhlet apparatus. The as-obtained polyphenolic-rich extract was employed for the preparation of silver nanoparticles (Ag−NPs). Under optimized reaction conditions viz 60 °C temperature and 500 μ l of extract solution (5 mg ml −1 ) highly disperse spherical nanoparticles of the average size of 15.8 ± 4.8 nm were obtained. Further, the optical band gap of Ag−NPs prepared using optimized reaction conditions was found to be 2.6 eV using the Tauc equation. Additionally, to understand the reduction by the extract, kinetic studies were also carried out which suggest the predominant occurrence of pseudo-first-order reaction. Furthermore, the mechanism of formation of Ag−NPs using major components of extract viz gallic acid and catechin which were identified by HPLC were also investigated using DFT. The mechanistic investigation was performed for both the keto-enol and radical-mediated preparation of Ag−NPs. Such theoretical investigations will help in the efficient designing of greener and novel routes for the synthesis of Ag−NPs. Additionally, the prepared silver was also employed for the colorimetric detection of H2 O2 .